School Social Workers’ Reports of Differences in Policies and Practices in Trauma-Informed and Non-Trauma-Informed Schools - Kate R. Watson; Ron Avi Astor; Gordon P. Capp; Rami Benbenishty (Behavioral Sciences)
This study explored trauma-informed schools from the perspective of social workers, documenting the reported practices and policies associated with trauma-informed approaches in U.S. schools. Survey data from 538 school social workers were analyzed to investigate the differences in policies and practices between schools identified as trauma informed and not. Logistic regression analyses examined whether the presence of specific school practices and policies was associated with the identification of a school as trauma informed. Of a wide array of programs and policies that may be present in trauma-informed schools, only the presence of trauma training and resources for secondary traumatic stress were key predictors of social workers’ identification of a school as trauma informed. The implementation of trauma training has long been the primary focus of trauma-informed approaches in schools. Should commitment to trauma-informed approaches endure, we recommend moving beyond training and secondary traumatic stress resources to deepen the field’s focus on implementing trauma-informed practices and policies at all organizational levels. We also recommend that future research looks carefully at how some school safety and trauma-informed approaches may be incompatible and the extent to which trauma-informed approaches improve or detract from children’s educational experiences and outcomes.